2007
DOI: 10.1007/s12020-007-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of testosterone with inhibin α and βA subunits to regulate prostate gland growth

Abstract: Testosterone regulation of prostate gland growth has been shown to involve reciprocal interaction with inhibin and activin. This study was therefore conducted to correlate the effect of testosterone on prostate gland proliferation and differentiation with the level of expression of inhibin alpha and betaA subunits. Immature dogs were treated with testosterone for 0, 3, 7, and 14 days and prostate gland growth was assessed by morphological and immunohistological localization of differentiation and proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This antiproliferative role of prostatic activin A may also be a defense mechanism against excess proliferation and hyperplasia. Activin ␤A subunit is present in the glandular epithelium of benign prostate hyperplasia in humans (278,420) and is induced by testosterone treatment in prepuberal dogs (389). However, many gaps remain in our knowledge of how activin A is regulated and whether it is implicated in the genesis of human prostatic disease.…”
Section: Prostatementioning
confidence: 99%
“…This antiproliferative role of prostatic activin A may also be a defense mechanism against excess proliferation and hyperplasia. Activin ␤A subunit is present in the glandular epithelium of benign prostate hyperplasia in humans (278,420) and is induced by testosterone treatment in prepuberal dogs (389). However, many gaps remain in our knowledge of how activin A is regulated and whether it is implicated in the genesis of human prostatic disease.…”
Section: Prostatementioning
confidence: 99%
“…The canine prostate does not seem to produce inhibin (Garde and Sheth, ), while the glandular epithelium synthesises activin A and TGF‐beta receptor II, whose expression declines rapidly after castration, demonstrating that their synthesis is androgen dependent (Al‐Omari et al., ). Indeed, treatment with testosterone increases the expression of activin in the prostate gland (Shidaifat et al., ). Activins act by inhibiting the proliferation of prostate cells both during and after morphogenesis (Cancilla et al., ).…”
Section: Tissue Distribution In Health and In Some Pathologic Conditionsmentioning
confidence: 99%
“…Previous results from rats (Mirosevich et al, 1999) and dogs (Shidaifat et al, 2007b) showed that testosterone treatment exerts a dual effect on prostatic cell proliferation characterized by an initial stimulation, followed by inhibition, of proliferation. The proliferation rate of the prostate gland in response to testosterone treatment appeared to be related to the differentiation status of prostatic cells (Shidaifat et al, 2007b). These results suggested that testosterone treatment acts to first drive prostatic cell proliferation and differentiation and then, when the cells become differentiated, it acts to maintain a low proliferation turnover rate of differentiated cells.…”
Section: Discussionmentioning
confidence: 96%